Community Answer

Honor CodeSolved 1 Answer

See More Answers for FREE

Enhance your learning with StudyX

Receive support from our dedicated community users and experts

See up to 20 answers per week for free

Experience reliable customer service

Get Started

by virtaal grand. concept inverting ferminal \left(\underline{V}=V_{I}\right)(1) cor apamp is equal to nominverting termimal \left(V_{t}=V_{N I}\right) & in opamp-1 \left.V_{a}\right) oxemp,2 \left(v_{b}\right) & oparma 3\left(v_{c}\right) are V_{I} \& V_{N I}also intermal carrent eb all opamp. i=09pply \mathrm{KCL} ab V_{C} rode (opamp-3) of V_{-}=V_{I}=V_{C}\begin{aligned}& \frac{V_{c}-V_{0}}{500 k^{c}}+\frac{V_{c}-V_{O_{1}}}{25 k}+i=0 \\\Rightarrow & V_{c-V_{0}}+20\left(V_{c}-V_{O_{1}}\right)+0=0 \\\Rightarrow & 21 V_{c}=V_{0}=20 V_{01} \quad, \quad(1) \Rightarrow V_{0}=21 V_{c-2}-2 V_{O_{1}}\end{aligned}Now \mathrm{ccl} of V_{C} at V_{t}=V_{I}\frac{v_{c}}{500 k}+\frac{v_{C}-v_{02}}{251 c} \neq i=0\begin{array}{l}v_{c}+20\left(v_{c}-v_{O_{2}}\right)=0 \\21 v_{c}-20 V_{2}=0 \\v_{O_{2}}=\frac{21 v_{c}}{20}-2\end{array}(2)\mathrm{KCl} of v_{a}\left(\right. opamp-1) v_{t}=v_{N_{I}}\begin{array}{l}\frac{v_{a}-v_{m}}{20 k^{c}}+\frac{v_{a}-0}{30 k}+i=0 \\3 v_{a}-3 v_{i n}+2 v_{a}=0 \\5 v_{a}=3 v_{i n} \\v_{a}=\frac{3}{3} v_{i n}\end{array}\mathrm{KCL} at V_{q} at V_{-}=V_{I} (oparom-1)\begin{array}{l}\frac{v_{a}-v_{0_{1}}}{10 k}+\frac{v_{a}-v_{b}}{2 k}+i=0 \\v_{a}-v_{0_{1}}+5 v_{a}-5 v_{b}=0 \\6 v_{a}-5 v_{b}=v_{01}\end{array}\mathrm{KCl} af V_{b} im (opamp-2) at V_{+}=V_{N_{I}}(3)\frac{V_{b}-0}{80 k}+\frac{V_{b}-V_{i n}}{40 k}+i=0\begin{array}{l}\Rightarrow \quad V_{b}+2 V_{b}-2 v_{i n} t_{0}=0 \\\Rightarrow \quad 3 v_{b}=2 v_{i n} \\\Rightarrow \quad v_{b}=\frac{2}{3} V_{i n}-3\end{array}\mathrm{kCl} at V_{b} in \left(\right. oparmp-2) at V_{-}=V_{I}\begin{array}{l}\frac{v_{b}-v_{a}}{2 k}+\frac{v_{b}-v_{02}}{10_{k}}+i=0 \\5 v_{b}-5 v_{a}+v_{b}-v_{02}=0 \\6 v_{b}-5 v_{a}=v_{02} \\6\left(\frac{2}{3} v_{i n}-5\left(\frac{3}{5} v_{i n}\right)=v_{02}\right. \\4 v_{i n}-3 v_{m}=v_{0_{2}} \\v_{i n}=v_{02}\end{array}Now from eqn & put value ab v_{a}=\frac{3}{5} \mathrm{Vm}_{\mathrm{m}} \& v_{b}=\frac{2}{3} v_{\mathrm{m}}\begin{array}{l}G v_{a}-5 v_{b}=v_{0 j} \\6\left(\frac{3}{5} v_{i n}\right)-5\left(\frac{2}{3} v_{i n}\right)=v_{01}\end{array}(4)from equn (2) v_{O_{2}}=\frac{21}{20} v_{C} but value ab v_{O_{2}}\begin{array}{ll}\Rightarrow \quad V_{i n}=\frac{21}{20} V_{c} \quad & \text { from ean (6) } \\\Rightarrow \quad & \left(V_{02}=V_{m}\right)\end{array}Now from ean 7 , (8), put value ab v vo, v_{1}, \$ v_{c} in term ab v_{i n} in eqn (\begin{array}{c}\Rightarrow 21 V_{c}-V_{0}=20 V_{0_{1}} \\\Rightarrow 21\left(\frac{20}{21} V_{i m}\right)-V_{0}=20\left(\frac{4}{5} V_{i m}\right) \\\Rightarrow 20 V_{i n}-V_{0}=16 V_{i n} \\\Rightarrow 20 V_{i n}-16 V_{i n}=V_{0} \\\Rightarrow 4 V_{i n}=v_{0} \\\Rightarrow 4 \frac{V_{0}}{V_{i n}}=4\end{array}thank you ...